EFFECT ABDOMINAL STRETCHING ON MENSTRUAL PAIN (DYSMENORRHEA) IN YOUNG WOMEN AT YUNIOR HIGH SCHOOL 1 DEPOK - Sasgia Rahmalia Chan, -; Desmawati (FIKES, UPNVJ, 2019)
Background: Menstrual pain or dysmenorrhea is a problem that is often faced by teenagers during menstruation. Dysmenorrhea occurs due to an imbalance of the hormone progesterone which causes uterine contractions and stimulate the pain response of each individual. Based on the underlying pathophysiology, there are two types of dysmenorrhea, namely primary dysmenorrhea and secondary dysmenorrhea. Primary dysmenorrhea occurs in women of childbearing age in the form of pain in the lower abdomen so that it can disrupt their quality of life. Dysmenorrhea often interferes with teenagers' productivity and influences coping abilities. The purpose of this study was to determine the effect of abdominal stretching on menstrual pain (dysmenorrhea) in adolescent. Methods: This research is a quasi-experimental study with a one group pretest posttest design approach. A total of 29 samples were taken by purposive sampling and stratified sampling technique in junior high school 1 Depok from March to June. The data analyzed in this study using the dependent t-test. Results: The results obtained P-Value 0,000 (P < 0,05) means that there is a significant effect the abdominal stretching exercises on intensity of menstrual pain. Conclusion: Abdominal stretching exercise is recommended to be another alternative for reducing dysmenorrhea in teenagers. That intervention is easy, safe and without side effects